Molecular Docking and ADMET Prediction Of Quinazoline Derivates As Potential Anti Cancer - Dewi, Tanaya Jati Dharma; Muchlashi, Luthfi Ahmad; Nastiti, Ginanjar Putri (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 3 (2025): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2026)
Objective: The objective of this study is to design some dimethyl amino substituent quinazoline derivatives as an anticancer with a computational method to obtain the interaction of the compound with tyrosine kinase as a protein target, as well as data related to ADMET of the compounds. Methods: A set of Compounds are designed and stabilized using ChemDraw and Chembio3D, docking and visualization using Molegro Virtual Docker, ADME prediction using pkCSm Tool online. Toxixcity prediction using Protox Online II. Molecular Docking Studies Were Carried Out On Tyrosine Kinase Protein In Order To Assesses Binding Affinity Results: Sixteen compounds of dimethyl amino substituent quinazolin derivatives docked with tyrosine kinase receptor (PDB ID: 1M17).Compound DAQ-2, DAQ-3 and DAQ-6 have rerank score at -99,70; -96,30;-99,30 lower than erlotinib which rerank score at -95,62. Compunds additionally evaluated from ADME predition and toxicity Conclusion: This study indicates that dimethyl amino quinazoline-3 (DAQ-3) has potential Tyrosine kinase inhibitor as anti cancer activity with lower toxicity